Continuously Flow Photothermal Catalysis Efficiently CO2 Reduction Over S‐Scheme 2D/0D Bi5O7I‐OVs/Cd0.5Zn0.5S Heterojunction with Strong Interfacial Electric Field. Issue 12 (1st January 2023) - Gao, Xiaoming; He, Hongbin; Zhu, Wei; Yang, Chunming; Xu, Kaixuan; Feng, Bingbing; Hu, Yanan; Fu, Feng
Abstract: Using CO2, water, and sunlight to produce solar fuel is a very attractive process, which can synchronously reduce carbon and convert solar energy into hydrocarbons. However, photocatalytic CO2 reduction is often limited by the low selectivity of reduction products and poor photocatalytic activity. In this study, S‐scheme Bi5 O7 I‐OVs/Cd0.5 Zn0.5 S (Bi5 O7 I‐OVs/CZS‐0.5) heterojunction with strong interfacial electric field (IEF) is prepared by in situ growth method. The performance of reduction CO2 to CO is studied by continuous flow photothermal catalytic (PTC) CO2 reduction platform. 12.5% Bi5 O7 I‐OVs/CZS‐0.5 shows excellent CO yield of 58.6 µmol g −1  h −1 and selectivity of 98.4%, which are 35.1 times than that of CZS‐0.5 under visible light. The charge transfer path of the S‐scheme through theoretical calculation (DFT), in situ irradiation Kelvin probe force microscope (ISI‐KPFM) and in situ irradiation X‐ray photoelectron spectroscopy (ISI‐XPS) analysis, is verified. The study can provide useful guidance and reference for improving activity by oxygen vacancy induced strong IEF and the development of a continuous flow PTC CO2 reduction system. Abstract : S‐scheme Bi5 O7 I‐OVs/Cd0.5 Zn0.5 S heterojunction with strong interfacial electric field (IEF) is prepared. The performance of reduction CO2 is studied by continuous flow photothermal catalytic platform, and CO yield of 58.6 µmol g –1  h –1 and selectivity of 98.4% is obtained. The study can provide useful reference for improving activity by oxygen vacancy induced strong IEF and the development of continuous flow photothermal catalytic CO2 reduction system.